2018
DOI: 10.1016/j.palaeo.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Late Middle Miocene volcanism in Northwest Borneo, Southeast Asia: Implications for tectonics, paleoclimate and stratigraphic marker

Abstract: Explosive volcanic events often produce pyroclastic materials that can be recognized from the geological record. These discrete pyroclastics form regional marker beds. Here we report the occurrence of a tephra layer interbedded within very thick coal beds near Mukah, Sarawak, Borneo. Traceable for tens of kilometers in the Mukah area of Sarawak, this tephra layer can be considered as regional stratigraphic marker with precise chronostratigraphic control. Systematic sedimentological, mineralogical, geochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…Murtaza et al (2018) concluded a Late Pliocene to Pleistocene age for the Liang Formation based on palynology. More recently, a tephra deposit within the coalfield has been dated by Ramkumar et al (2018) and revealed a latest Middle Miocene age (c. 12 Ma), thus indicating a slightly older age for the sequence than previously assumed, and a correlation with the Liang Formation in the northern Miri Zone/Brunei therefore seems inappropriate.…”
Section: Previous Stratigraphymentioning
confidence: 89%
See 2 more Smart Citations
“…Murtaza et al (2018) concluded a Late Pliocene to Pleistocene age for the Liang Formation based on palynology. More recently, a tephra deposit within the coalfield has been dated by Ramkumar et al (2018) and revealed a latest Middle Miocene age (c. 12 Ma), thus indicating a slightly older age for the sequence than previously assumed, and a correlation with the Liang Formation in the northern Miri Zone/Brunei therefore seems inappropriate.…”
Section: Previous Stratigraphymentioning
confidence: 89%
“…2b and 3. The age of the Liang Formation in the Mukah-Balingian province is latest Middle Miocene as defined by the interbedded tephra layer reported by Ramkumar et al (2018).…”
Section: Revised Stratigraphymentioning
confidence: 93%
See 1 more Smart Citation
“…The Balingian Formation was initially considered to be Late Miocene based on foraminifera assemblages (Liechti et al, 1960) resulting in an estimated Early Pliocene and Late Pliocene to Pleistocene age for the overlying Begrih and Liang Formations respectively. However, recent U-Pb dating of zircons from a tuff layer in the Liang Formation (Ramkumar et al, 2018) yielded 11.4 ± 0.4 to 11.8 ± 0.8 Ma mean ages (late Middle Miocene) which enabled more precise stratigraphic positioning for the whole Mukah-Balingian sequence and highlights the importance of absolute age dating of critical horizons.…”
Section: The Nyalau Unconformitymentioning
confidence: 99%
“…The whole Borneo Island sits within the Sundaland region (Metcalfe, 2011). Although Borneo is not one of the most active regions of Sundaland, with only sparse earthquake and volcanic events today, it had a violent tectonic history (Mathew et al, 2016, b;Ramkumar et al, 2018). The basement of Borneo, at the western interior zone, consists of Palaeozoic and Mesozoic igneous, sedimentary, and metamorphic rocks that behaved as a craton during the middle to late Tertiary (Hall, 1996).…”
Section: Geological Historymentioning
confidence: 99%